Basa Enterprise : Banana Slice Machine / Muhammad Aqil Ziqry Nor M Zi ...[et al.] - Nor M Zi, Muhammad Aqil Ziqry; Azman, Muhammad Akmal; Ariffin, Muhammad Rafiq Amsyar; Zainuddin, Noor Syahida (2019)
BASA ENTERPRISE sells and repair a product called Banana Chip Machine. This business proposal presents our business description, activities and goals within three years forecasted business period. Our company guarantees that our products is affordable our product comes with service such as maintenance and spare part. We provide free maintenance service for the first 6 months. This will help user to have less worry about the cost if the machine has a breakdown. Plus, it is unlikely that the machine to have any problem in the first year operating due to it can only handle medium production rate. We also provide spare part for the machine in case the machine has broken part such as the motor.